Alar-Spanning Suture for Tip Contouring in Closed Approach Rhinoplasty for African–Caucasian Noses - Cedin, Antonio Carlos (Facial Plastic Surgery, 2013)
The alar-spanning suture is one of the easiest techniques for correcting the width of the alar complex that reduces the bulbous tip of African–Caucasian patients. This conservative technique does not weaken the lateral crura and yields long- term predictable results. Rhinoplastic surgeons should keep in mind this useful and reliable tool in their options for refinement of these challenging wide tips and not create so dramatic a change that the appearance is not consonant with the patient's ethnic heritage. Despite cosmetic surgeons usually performing it through an external columellar incision approach, it is possible, in many cases, to do it in a closed access, and thus avoid the risk of hyperpigmentation or hypertrophic scarring.
Keywords: alar-spanning; suture; tip; nose